Análisis de la Calidad de Servicios (QoS) en la Telefonía IP del Gobierno Autónomo Descentralizado Municipal del Cantón Montalvo - León Contreras, Mónica Gianella (2017)
At present, we live in a world of constant changes where the internet has become the most widely used communication tool worldwide being a fundamental part of people and large companies, generating greater benefits for society and at lower cost. IP telephony is an internet service that is responsible for providing voice transmission over technological infrastructures; allowing to reduce costs that is generated if a public telephone network (PSTN) is used. The following case study analyzes the integrity of the data using QoS when traveling through the Municipal Decentralized Autonomous Government network of Canton Montalvo, when telephone calls are made on IP services; through the use of mobile or digital phones. Free software such as Linux Centos, Asterisk and Zoiper were used to provide higher performance, high availability and data stability; also will be used mikrotik routers that will allow to make calls in networks LAN and WAN. By using this technology you will get great benefits with respect to the quality of services due to the priority that is set, so that will increase the speed and availability in the network.